2010
DOI: 10.2165/11318200-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Healthcare Payments and Impoverishment in the Occupied Palestinian Territory

Abstract: The inability of the Palestinian healthcare system to protect against the financial risks of ill health could be attributed to the prevailing sociopolitical conditions of the occupied Palestinian territory, and to some intrinsic system characteristics. It is recommended that pro-poor financing schemes be pursued to mitigate the negative impact of the recurrent health shocks affecting Palestinian households.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Due to a lack of consensus in domestic and international literature concerning the best methodology for calculating such expenditure, three different forms of calculations, widespread in literature, were employed: methodology proposed by Xu et al 21 (2003), used by Wagstaff & Van Doorslaer 19 (2003), and a variation of the Wagstaff & Van Doorslaer methodology. 7 , 12 Thus, a more deep understanding of the phenomenon in the country is possible as well as better comparison of results with findings from other countries.…”
Section: Methodsmentioning
confidence: 99%
“…Due to a lack of consensus in domestic and international literature concerning the best methodology for calculating such expenditure, three different forms of calculations, widespread in literature, were employed: methodology proposed by Xu et al 21 (2003), used by Wagstaff & Van Doorslaer 19 (2003), and a variation of the Wagstaff & Van Doorslaer methodology. 7 , 12 Thus, a more deep understanding of the phenomenon in the country is possible as well as better comparison of results with findings from other countries.…”
Section: Methodsmentioning
confidence: 99%
“…Leive and Xu (2008) [14] examined how households in 15 African countries characterized by low government health spending and lack of health insurance, cope with health shocks. 5 In 12 countries, high inpatient spending increased the likelihood of borrowing or selling assets. They also found that the high-income quintiles were less likely to use coping strategies relative to the poorest households.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also found that lower-income and rural households face greater financial risk. In another study, Mataria et al (2010) [5] examined the incidence and intensity of catastrophic and impoverishing healthcare payments borne by Palestinian households between 1998 and 2007. They found a low incidence of catastrophic health payments with only 1% of the surveyed households spent more than 40% of their total household expenditures (net of food expenses) on healthcare in 1998; however, the percentage was almost doubled in 2007.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Although budget share (share of healthcare payments from total income/consumption) is used extensively in the current studies, there is no consensus on the threshold of catastrophic payments in the literature. The current studies 11,16,17,25,[29][30][31][32] have used the threshold between 3% of budget share to 40% of the capacity to pay (ie, income/consumption minus subsistence expenditure requirements). Similar to the threshold ranges used in the Statistics Canada's report, 33 we used 3 and 6% of household consumption as the cut-off.…”
Section: Ethical Issuesmentioning
confidence: 99%